Impact of the social programs of the State Social Development Secretariat (SEDESOL) from 2018-2022, on poverty in the State of Yucatan. - Moo Novelo, Carlos Antonio (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To describe the impact of the programs implemented by SEDESOL on the levels of poverty that occur in the state of Yucatan.MATERIAL AND METHOD: The research approach was quantitative, correlational type, since the statistical information of the social programs that the state SEDESOL has implemented from 2018-2022 was obtained, identifying the beneficiaries, in order to facilitate their analysis, the linear regression was carried out for which the SPSS statistical package was used.RESULTS: The variables that can have the greatest impact on reducing poverty are increasing people's access to health services, as well as granting more social credits to people to boost their activities.CONCLUSIONS: Trying to reduce poverty with the programs is possible, as long as it is thought in improving education, health services, food, and access to better income, but it also requires constant monitoring, as well as a correct implementation, to truly benefit those who really need it.
Keywords: Social programs; Linear regression; Poverty; Public policies.